The role of antibodies in tuberculosis - Jacobs, Ashley (Department of Medicine, 2025)
The role of antibodies in tuberculosis (TB) has been debated for over a century. Antibodies against Mycobacterium tuberculosis (M.tb) are detectable in persons who appear to resist M.tb infection, and yet humoral immune activation is a consistent biomarker of TB disease progression. Antibody responses to TB could therefore be a dual-edged sword, whereby antibodies promote TB pathogenesis, but some people produce antibodies that contribute to immunity against M.tb. In this thesis, I have therefore investigated the role of antibodies in TB in multiple clinical cohorts. Firstly, I generated fully human monoclonal antibodies (mAbs) against M.tb from patients with ATB. I identify the antigen of one mAb as the secreted antigen GlnA1, and then show that this mAb promotes in vitro production of TNF-α, IL-6, and IL-1β in the absence of mycobacterial killing. Secondly, I investigated antibody responses against M.tb in persons who live with HIV (PLWH). PLWH fail to mount a significant increase in IgG levels against M.tb in ATB. M.tb-specific IgG responses are also detectable in different cohorts of PLWH with negative interferon gamma release assay (IGRA) tests. However, greater levels of M.tb-specific IgG associates with IGRA conversion. Thirdly, I showed the development of flow cytometric assays to study opsonization and antibody dependant cellular phagocytosis (ADCP) of live mycobacteria in BCG vaccinated adults. These methods show that BCG vaccination induces ADCP 28 days post-vaccination. Fourthly, I tested whether unswitched memory B cells, and specifically the marginal zone B cells (MZB) subset, are impacted by ATB. MZB respond to capsular pathogens and could thus recognize the M.tb cell wall. MZB are found to be depleted in ATB but are not enriched at the site of disease in PLWH with pericardial TB. The depletion of unswitched memory B cells in TB observed in this study resembles that reported in autoimmune disease. Taken together, I provide support to the notion that at least some antibodies against M.tb could contribute to immunopathology in TB. The fact that PLWH are at greater risk of disseminated TB, and mount less of an antibody response, however, supports a role for antibodies in preventing disseminated disease that remains to be studied.